PLX-PAD Cell Treatment of Critical Limb Ischaemia: Rationale and Design of the PACE Trial - Norgren, Lars; Weiss, Norbert; Nikol, Sigrid; Hinchliffe, Robert J.; Lantis, John C.; Patel, Manesh R.; Reinecke, Holger; Ofir, Racheli; Rosen, Yael; Peres, Dan; Aberman, Zami (European journal of vascular and endovascular surgery, 2019)
Critical limb ischaemia (CLI) is a life threatening condition with a considerable risk of major amputation and death. Besides revascularisation, no treatment has been proven to reduce the risks. Therapeutic angiogenesis by gene or cell therapy has not demonstrated definitive evidence in randomised controlled trials. PLX-PAD is an “off the shelf” allogeneic placental derived, mesenchymal like cell therapy, which, in preclinical studies, has shown pro-angiogenic, anti-inflammatory, and regenerative properties. Favourable one year amputation free survival (AFS), and trends in reduction of pain scores and increase of tissue perfusion have been shown in two small, open label, phase I trials. The PACE study is a phase III randomised, double blind, multicentre, multinational placebo controlled, parallel group study to evaluate the efficacy, tolerability, and safety of intramuscular injections of PLX-PAD cells to treat patients with atherosclerotic CLI with minor tissue loss (Rutherford Category 5) up to the ankle level, who are unsuitable for revascularisation or carry an unfavourable risk benefit for that treatment. The study will enroll 246 patients, who after screening are randomised in a ratio of 2:1 to treatment with intramuscular injections of PLX-PAD 300 × 106 cells or placebo on two occasions, eight weeks apart. The primary efficacy endpoint is time to major amputation or death (amputation free survival), which will be assessed in follow up of at least 12 months and up to 36 months. Based on favourable pre-clinical and initial clinical study results, the PACE phase III randomised controlled trial will evaluate placenta derived PLX-PAD cell treatment in patients with critical limb ischaemia, with an unfavourable risk benefit for revascularisation. Clinicaltrials.gov: NCT03006770.